Single crystals of mixed Br/Cl and Sn-doped formamidinium lead halide perovskites via inverse temperature crystallization. Issue 7 (22nd January 2020) - Ng, Michael; Halpert, Jonathan E.
Abstract : FAPbBr3− x Cl x and doped FAPb1− x Sn x Br3 perovskite single crystals were synthesized using inverse temperature crystallization (ITC). The single crystals displayed a bandgap tuneability of 2.05 eV to 2.57 eV and trap densities between 10 9 to 10 11 cm −3 . Abstract : Hybrid organic–inorganic perovskite mixed halides of FAPbBr3− x Cl x and doped FAPb1− x Sn x Br3 were synthesized using a generalized inverse temperature crystallization (ITC) method. With an appropriate choice of solvents and crystallization temperatures we show that large millimeter sized single crystals of these hybrid perovskites can be grown in a matter of hours to days using ITC. The structural and optical properties of these single crystals were characterized systematically. The mixed metal and mixed halide perovskites displayed a compositional bandgap tuneability in the region of 2.05 eV to 2.57 eV. The electrical properties of the perovskite single crystals were determined using a space-charge limited current (SCLC) method. The trap density determined from SCLC was between 10 9 and 10 11 cm −3 for all perovskites which is exceptionally low. The mobility was found to increase by one order of magnitude on the addition of only 3% Sn for FAPb1− x Sn x Br3 based perovskites which shows promise for enhancing the electrical properties. This demonstrates the generalizability of the ITC method to grow large high-quality perovskite single crystals with enhanced optical and electrical properties. In addition, it was observed for FAPbBr3− x Cl x based perovskites that initially degraded surfaces with suppressed PL emission could be repaired by using an anti-solvent treatment re-enabling the PL emission. Other perovskite compounds did not display any degraded surfaces and exhibited excellent stability in ambient conditions.